Eat this, not that, for kids : be the leanest, fittest family on the block! - Zinczenko, David (Rodale, 2008)
This must-have guide for concerned parents offers detailed analysis and nutritional tips on thousands of the most popular food choices for kids. Covering the best and worst options available at the most popular restaurants in the country as well as the healthiest--and most harmful--foods in the supermarket aisles, if kids are eating it, this book is probably analyzing it. Other features include: restaurant report cards on the best chain restaurants for your kids; drink this, not that! for kids; the 20 worst kids' meals in America; 10 "healthy" foods that aren't; and, the 8 foods you should feed your kid every day.